Developing Educational Games Based on PjBL to Improve Science Literacy - Riris Ermiyawati; Ana Fitrotun Nisa; Akbar Al Masjid (Postgraduate, University of Mataram, 2025)
Students' scientific literacy skills are still categorized as very low, this occurs due to the lack of innovative learning media capable. This research aims to develop educational games based on Project Based Learning (PjBL) to improve the scientific literacy of elementary school students. This research is a type of development research (R&D) with the ADDIE development model. The methods used in this research are quantitative and qualitative methods. Data were collected through model validation assessment sheets, implementation observations, and documentation. The model was tested on 115 fifth-grade students from three elementary schools in Kulon Progo Regency. Data were analyzed quantitatively and qualitatively, then analyzed inferentially with a paired sample t-test. The results of the study indicate: (1) the validation of the educational game product obtained an average score of 89.91% from experts and 82.82% from practitioners and (2) The analysis results show a probability value of 0.00 < 0.05, meaning there is a difference between the results of the pretest of science literacy skills and the posttest. So it can be concluded that the development of PjBL-based educational games is proven to be valid, feasible, and effective in improving the scientific literacy of elementary school students.